Lower airway inflammatory responses to high-intensity training in athletes - Boulet, L. P.; Turcotte, H.; Langdeau, J. B.; Bernier, M.-C. (Clinical and Investigative Medicine, 2005)
Purpose: There is an increased prevalence of asthma and airway hyperresponsiveness in elite athletes, particularly in swimmers. High intensity exercise may induce airway inflammation and subsequent remodelling in these subjects. Our aim was to evaluate the effects of high-intensity training on induced-sputum cell populations in elite athletes. Methods: Swimmers and runners with hyperresponsive airways (SH and RH), defined by a provocative concentration of methacholine inducing a 20% decrease in FEV1 (PC20) <16 mg/ml or with normoresponsive airways (PC20 > 16 mg/ml; SN, RN) to methacholine were enrolled. The mean PC20 was 2.27 mg/ml in SH (n=12), 32.2 in SN (n=10), 3.25 in RH (n=10) and 41.5 in RN (n=13). All athletes had two induced sputum analyses at one- to two-week intervals in random order: after a period of 72 hours without training, 24 hours after a training session. Results: PC20 was unchanged after training. The median % neutrophils and eosinophils in groups SH, SN, RH, and RN, respectively, were 26.5-1.6, 8.6- 0.3, 28.0-0.03 and 25.5-0.1 before and 45.0-0.5, 31.1-0.4, 54.0-0.6 and 48.3-0.3 after training. While the magnitude of the increase in neutrophils was similar for all groups, it reached statistical significance (pre-post-training) only in the SH group (P = 0.039). Conclusion: A one-hour session of high-intensity training was associated with an increase in airway neutrophils among hyperresponsive swimmer athletes, while airway responsiveness remained unchanged in all groups. Asthma is one of the most common chronic respiratory ailments worldwide and its prevalence has been increasing over the past two decades.1 It is defined as an airway disease characterized by reversible airflow limitation and airway hyperresponsiveness (AHR), attributed to an inflammatory process and its consequences on airway structure.2 The asthmatic syndrome is thought to develop most often after exposure to environmental substances inducing an airway inflammatory process.3 Among the main types of environmental hazards leading to asthma are allergens, in atopic subjects, and other sensitising or toxic substances, most often found at the workplace, with irritant properties to the airways.4,5 When the first symptoms of asthma appear, airway inflammation may have been present for many months or years.6,7 In susceptible individuals, this ongoing inflammatory process can lead to changes in airway responsiveness, either directly, from its effects on airway mechanics, or indirectly, through changes in the bronchial structure. The finding of considerable airway inflammation and remodelling both in mild recently diagnosed asthmatic patients and in subjects with asymptomatic AHR support these hypotheses, these processes increasing with the development of symptomatic asthma in this last group.8 Subjects with asymptomatic AHR who developed asthma symptoms had an increase in airway inflammatory cells on bronchial biopsies, with an increase in CD4+/CD8+ ratio similar to that found in asthmatic patients. They also showed an increase in subepithelial collagen deposition, its thickness becoming similar to that of asthmatic subjects. Although exercise of short duration does not seem to induce significant airway inflammati on, the same cannot be said with certainty for prolonged strenuous exercise.9,10 Repeated intense exercise may alter many functions of the immune, endocrine or cardiovascular systems.11 There is increasing evidence that high-level exercise may also influence the respiratory system and induce airway function changes12,13, although the mechanisms explaining the increased prevalence of AHR and asthma reported in athletes remain to be determined. In a previous study, we found a marked increase in the prevalence of AHR in swimmers and, to a lesser extent, in athletes training in cold air, compared with long-distance runners.12 We proposed that, for these groups, the chronic intense inhalation of chlorine derivatives or of cold air could induce an airway inflammation and subsequent remodelling. In runners, other factors, such as inhalation of allergens or drying of the airways after marked increases in ventilation, may affect airways, but in our study, the prevalence of AHR was similar to that of controls. Although previous publications have looked at the effects of exercise, performed on a treadmill or ergometer, on airway inflammation in non-athletes, in light of the increased prevalence of asthma and AHR in high-level athletes, particularly swimmers, we thought it was important to explore short-term effects of intense exercise in this population further. Therefore, the goal of this study was to determine the influence of high-intensity exercise on airway inflammation and function of swimmers in comparison with runners, two groups of athletes training in different environmental conditions.